Malay Muslims Patani Insurgency Pattern in the Post-Revolution 1932 - Ahmad Syukri (Jurnal Studi Sosial dan Politik, 2019)
Malay Patani is a majority resident in southern Thailand. They have a long history of the insurgency. The history of the Malay insurgency of Patani lasted since the 18th century. In the early 21st century, the Malay insurgency pattern was likely to strengthen in response to the policies of the Thai regime repressive to insurgency issues and strict assimilation policies that demanded an all-ethnic identity in Thailand is the true ethnic Thai identity. In this literature study, Malay Patani insurgency pattern after revolution 1932 because of the will to restore the rights and integrity of Malayu Patani culture. It is the main reason for the rejection of Malay nationalism Patani by the Thai regime. In the last decade, the concept of Islam as identity has increasingly made it a determination to establish the Malay identity of Patani Islam as the basis of the insurgency movement